Synthesis, Magnetic Properties and X-ray Analysis of Zn0.97X0.03O Nanoparticles (X = Mn, Ni, and Co) using Scherrer and Size-Strain Plot Methods - Zak, A.K.; Abd Majid, Wan Haliza; Abrishami, M.E.; Yousefi, R.; Parvizi, R. (2012)
Un-doped and doped ZnO nanoparticles (Zn0.97X0.03O-NPs, X = Mn, Co, and Ni) were synthesized from a metal acetate precursor and acetic acid by a modified sol gel combustion method. The compounds were synthesized at calcination temperatures of 650 degrees C for 1 h. The synthesized un-doped/doped ZnO-NPs were characterized by X-ray diffraction analysis (XRD) and high-magnification transmission electron microscopy (TEM). The XRD results revealed that the sample product was crystalline with a hexagonal wurtzite phase. The TEM showed ZnO-NPs nearly spherical shapes and a non-uniform shape for doped ZnO-NPs. The crystalline development in the ZnO-NPs was investigated by X-ray peak broadening. The size strain plot (SSP) method was used to study the individual contributions of crystallite sizes and lattice strain on the peak broadening of the un-doped and doped ZnO-NPs. Physical parameters such as strain, stress and energy density values were calculated more precisely for all reflection peaks of XRD corresponding to the wurtzite hexagonal phase of ZnO lying in the range of 20-80 degrees from the SSP results. The vibrating sample magnetometer (VSM) was also used to study the magnetic behavior of the samples in the ceramic form. The obtained results showed that strain play an important role in peak broadening; moreover, the mean crystalline size of the un-doped and doped ZnO-NPs estimated from the TEM and the SSP method were highly inter-correlated. (C) 2012 Elsevier Masson SAS. All rights reserved.